PENGUATAN KEPEMIMPINAN VISIONER DAN MOTIVASI KERJA DALAM UPAYA MENINGKATKAN KREATIVITAS GURU - Erni Sukmayanti; Nandang Hidayat; Herfina Herfina (JURNAL MANAJEMEN PENDIDIKAN, 2021)
STRENGTHENING VISIONARY LEADERSHIP AND WORK MOTIVATION INEFFORTS TO INCREASE TEACHER  CREATIVITYThis study aimed to find the relationship between teacher creativity increase and visionary leadership strength, as well as between teacher creativity and and work motivation. This research was conducted in 11 private junior high schools in Megamendung District, Bogor Regency with a sample of 113 honorary teachers. This study used the correlational analysis method to determine the strength of the relationship between the variables studied and SITOREM analysis to analyze the indicator variables. The results of the study resulted in teacher creativity were: Ŷ = 1,122 + 0,148X1 + 0,750X2.  X1 is visionary leadership and X2 is work motivation. The optimal solution produced were: there were 10 indicators that have already been good so that they were maintained or developed, namely; responsibility, gaining recognition, flexible thinking, curiosity, classroom environment, future orientation, innovation, exemplary, communication, work commitment. There were 5 indicators that were still weak so it needed to be improved in the following order of improvement, such as: pride in work, opportunity to advance, achievements achieved, love to learn new things, opportunity to solve problems. Based on those findings, it can be concluded that strengthening visionary leadership and work motivation could increase teacher creativity.